Tumor-targeted micelle-forming block copolymers for overcoming of multidrug resistance - Braunová, Alena; Kostka, Libor; Sivák, Ladislav; Cuchalová, Lucie; Hvězdová, Zuzana; Laga, Richard; Filippov, Sergey; Černoch, Peter; Pechar, Michal; Janoušková, Olga; Šírová, Milada; Etrych, Tomáš (Journal of controlled release, 2017)
New amphiphilic diblock polymer nanotherapeutics serving simultaneously as a drug delivery system and an inhibitor of multidrug resistance were designed, synthesized, and evaluated for their physico-chemical and biological characteristics. The amphiphilic character of the diblock polymer, containing a hydrophilic block based on the N-(2-hydroxypropyl)methacrylamide copolymer and a hydrophobic poly(propylene oxide) block (PPO), caused self-assembly into polymer micelles with an increased hydrodynamic radius (Rhof approximately 15nm) in aqueous solutions. Doxorubicin (Dox), as a cytostatic drug, was bound to the diblock polymer through a pH-sensitive hydrazone bond, enabling prolonged circulation in blood, the delivery of Dox into a solid tumor and the subsequent stimuli-sensitive controlled release within the tumor mass and tumor cells at a decreased pH. The applicability of micellar nanotherapeutics as drug carriers was confirmed by an in vivo evaluation using EL4 lymphoma-bearing C57BL/6 mice. We observed significantly higher accumulation of micellar conjugates in a solid tumor because of the EPR effect compared with similar polymer-drug conjugates that do not form micellar structures or with the parent free drug. In addition, highly increased anti-tumor efficacy of the micellar polymer nanotherapeutics, even at a sub-optimal dose, was observed. The presence of PPO in the structure of the diblock polymer ensured, during in vitro tests on human and mouse drug-sensitive and resistant cancer cell lines, the inhibition of P-glycoprotein, one of the most frequently expressed ATP-dependent efflux pump that causes multidrug resistance. In addition, we observed highly increased rate of the uptake of the diblock polymer nanotherapeutics within the cells. We suppose that combination of unique properties based on MDR inhibition, stimuli sensitiveness (pH sensitive activation of drug), improved pharmacokinetics and increased uptake into the cells made the described polymer micelle a good candidate for investigation as potential drug delivery system.
Keywords: Animals; Doxorubicin; Drug Resistance, Neoplasm; mnohočetná léková rezistence; tumor burden; Female; Propylene Glycols; Hydrophobic and Hydrophilic Interactions; Cell Line, Tumor; akrylamidy; protinádorová antibiotika; ženské pohlaví; Micelles; Neoplasms; nádory; Drug Carriers; Polymers; lidé; Tumor Burden; Mice; chemorezistence; Antibiotics, Antineoplastic; Drug Liberation; Drug Resistance, Multiple; myši; propylenglykoly; Acrylamides; hydrofobní a hydrofilní interakce; doxorubicin; micely; polymery; nosiče léků; Cell Survival; zvířata; uvolňování léčiv; viabilita buněk; Mice, Inbred C57BL; nádorové buněčné linie; myši inbrední C57BL; Humans